Bibliometric and Network Analysis of Corporate Tax Avoidance Developments Using VOSviewer - Sa'adah, Fiki Labibatus; Andriani, Sri (Pajak dan Manajemen Keuangan, 2025)
The purpose of this study is to determine the trends and developments in corporate tax avoidance studies using a mixed method approach. This method includes a quantitative approach in bibliographic analysis and literature review. Data were collected through searching national and international journals indexed in Emerald, Springer, and Scopus by referring to relevant publications. Data analysis includes: (1) mapping trends and developments in corporate tax avoidance research with Vosviewer software based on bibliographic studies; and (2) identifying trends and issues in corporate tax avoidance through literature review. The results of the Vosviewer analysis found five large groups with 40 main topics after selection. All topics are explained comprehensively through a literature review. This study provides a comprehensive picture of themes that are often studied in previous literature, thus becoming a reference for further research.